Avaliação da penetração de íons cloreto em concretos produzidos com escória de alto forno e agregados miúdos reciclados de resíduo de concreto fresco - Priscylla Botelho Athayde (2020)
The recycled aggregates from construction and demolition waste (CDW) have great diversity and heterogeneity in their composition. These are, undoubtedly, the main difficulties faced to include in the normative system, criteria for the production and use of concretes with structural purpose obtained from the incorporation of such materials. Despite the challenges faced, several studies have been carrying out in order to investigate the potential for using CDWs. Within this context, divergent results of mechanical strength was reported in researches carried out with concretes produced with materials obtained from ready-mixed concrete plants waste, in particular, the fresh concrete waste, residual material from returned concrete and wastes obtained by ready-mixed plant elements washing operations. It should also be noted that, in order to guarantee the material performance over the useful life of the structural elements, it is necessary to investigate not only its mechanical characteristics, but also, among other aspects, its durability due to the interaction with aggressive agents of the environment to which it will be exposed. Since the penetration of chloride ions is one of the main factors responsible for reducing the useful life of reinforced concrete structures, the present work aims to evaluate the performance of concretes produced with the partial replacement of natural fine aggregates for recycled fine aggregates from the processing of fresh concrete waste due to the penetration of such ions. For this purpose, two reference concretes were produced using Portland cements containing 0% and 60% contents of granulated blast furnace slag, which were dosed with an water/cement ratio ≤ 0.55 for a compressive strength ≥ 30 MPa, in order to comply the performance requirements for reinforced concrete established for the environmental aggressiveness class III of NBR 6118 (ABNT, 2014). For each of the reference concretes, two other concretes mixes were dosed with the partial replacement of 30% and 50%, by weight, of natural fine aggregates by recycled fine aggregates. The specimens were produced according to the procedure defined by NBR 5738 (ABNT, 2015) and maintained in a condition of saturated cure until the date of the tests. The resistance of concretes to the penetration of chloride ions was evaluated at the ages of 28, 63, 91, 126 and 182 days, using samples obtained from cylindrical specimens, and tested according to the procedure established at the Finnish NT standard BUILD 492 (NORDTEST, 1999). Furthermore, complementary tests were carried out to determine the water absorption by capillarity and by immersion, the voids index and specific masses, as well as mechanical strength tests. The results obtained demonstrated, firstly, that the partial replacement of 60% of Portland cement by granulated blast furnace slag brought relevant improvements in all the investigated properties. It was observed that, in the most advanced ages, the partial substitution of natural fine aggregates for recycled fine aggregates and Portland cement for blast furnace slag, implied, simultaneously, in an increase in mechanical strength and an improvement in the physical properties and durability of the concretes. Thus, based on the results obtained in this study, it was found that the concretes produced presented satisfactory performance, both in the mechanical aspects as well as in the evaluated durability requirements to be used for structural purposes.